PROFESSIONAL SELF-IMPROVEMENT OF FUTURE MASTERS OF PHYSICAL EDUCATION IN THE PROCESS OF EDUCATIONAL AND COGNITIVE ACTIVITIES (Physical Culture and Sport: Scientific Perspective, 2023)
The scientific and methodological literature was analyzed and the theoretical and practical aspects of this problem were considered. Forms of implementation of the organizational and pedagogical condition are determined: assistant pedagogical practice (use of mental maps); scientific and research work (the activity of a student scientific and research circle is organized); "Round table" in the form of a debate. Assistant teaching practice is an effective form of realization of acquired theoretical knowledge, abilities, skills and a means of professional development of the future specialist, which helps to understand that the desire for self-improvement is the most important feature of the future specialist, pushes and stimulates the master's student to future professional activity.Research work is a prerequisite for the successful operation of higher educational institutions, one of the most effective forms of work for future masters of physical education. It forms the ability to use modern technologies to collect information, process experimental and empirical data, and master modern research methods. "Round table" as a form of cognitive activity of master's students allows you to consolidate previously acquired knowledge, forms the ability to solve problems, strengthen positions, teaches the culture of conducting a conversation.Testing "Diagnostics of the need for self-improvement" was experimentally carried out in order to find out the characteristics of behavior in various situations and changes in the degree of expression of the need for self-improvement. A comparison of indicators of the need for self-improvement of the control and experimental groups was made, and the dynamics of changes in the degree of expression of the need for self-improvement were also shown.
Keywords: professional self-improvement; pedagogical practice; independent work; research work; future master's degree in physical education